Bridging The Gap Between Civil Engineering Education And Industry Requirements: Evidence From Indonesia - Ahmad Haedar Rifqi; Bayu Kurniawan (CV. SINAR HOWUHOWU, 2026)
The mismatch between higher education outcomes and industry requirements has become a critical issue, particularly in developing countries such as Indonesia. This study aims to examine the gap between civil engineering education and the competencies required by the construction industry. A mixed methods approach was employed, combining quantitative data from questionnaire surveys and qualitative insights from in-depth interviews with graduates, academics, and industry practitioners. The quantitative analysis utilized gap analysis to identify discrepancies between acquired and required competencies, while thematic analysis was applied to interpret qualitative findings. The results indicate that although civil engineering graduates possess adequate theoretical knowledge, they lack practical skills and essential soft skills such as communication, teamwork, and problem-solving. The largest gaps were identified in non-technical competencies, highlighting the need for a more balanced curriculum. Additionally, factors such as limited industry collaboration, rigid curricula, and insufficient integration of modern technologies contribute significantly to the mismatch. This study emphasizes the importance of strengthening collaboration between universities and industry through internships, project-based learning, and curriculum co-development. Integrating digital tools and soft skills training into academic programs is also essential to enhance graduate employability. The findings provide valuable insights for policymakers, educators, and industry stakeholders in developing more responsive and industry-aligned civil engineering education systems in Indonesia.